Direction of Trade Statistics : December 2016. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2016)
This December 2016 quarterly issue of Direction of Trade Statistics (DOTS) provides, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The availability of partner data makes it possible to include in direction of trade statistics (DOTS) estimates for current months not only for countries less current or frequent in their reporting but also for countries for which data are not obtainable from other sources. Country pages include lines for all partner countries that have been reported, estimated, or extrapolated. As a result of reporting and processing lags, trade data for a given period are often released before all customs documents for the period have been processed.